Chiral determination of 3, 4-methylenedioxypyrovalerone enantiomers in rat serum. Issue 4 (11th January 2017) - Hambuchen, Michael D.; Hendrickson, Howard P.; Owens, S. Michael
Abstract : A chiral-selective LC-MS/MS method for determination of MDPV, a drug of abuse with enantiomerically selective pharmacology, was developed and validated. Abstract : The emerging stimulant drug of abuse (3, 4)-methylenedioxypyrovalerone [( R, S )-MDPV] is self-administered as a racemic mixture by intranasal, iv, oral, and smoking routes. The individual enantiomers are known to have widely different pharmacological effects, with ( S )-MDPV showing much greater potency than ( R )-MDPV in pharmacological testing. The goal of these studies was to develop and validate an analytical method for quantitation of ( R )-MDPV, ( S )-MDPV and ( R, S )-MDPV in small volumes of rat serum using a chiral separation column and liquid chromatography-mass spectrometry. The method was validated for selectivity, precision, accuracy, recovery, sensitivity, and reproducibility. The method was also used to determine the enantiomeric stability of the individual enantiomers during sample cleanup and analysis. The linear dynamic range of the calibration curve was 1–1000 ng ml −1 for each enantiomer. Concentration values for the lower limit of quantitation (1 ng ml −1 ) were within 30% of their nominal value, but all other calibration standards were <20% of their nominal value. With proper storage and handling of samples, the two MDPV enantiomers were shown to remain stable in rat serum without any apparent racemization during the time needed for analysis. Finally, the ruggedness of the method was demonstrated with diluted and undiluted serum samples collected from Sprague Dawley rats in a preliminary pharmacokinetic study at 3 mg kg −1 of ( R, S )-MDPV. In summary, the assay used a simple sample preparation method, reversed-phase chiral chromatography, and tandem mass spectrometry to achieve accurate and selective determinations of MDPV enantiomer concentrations in small volumes of serum.